Effects of broodstock conditioning diets on the early life stages of Atlantic cod (Gadus morhua) - McKenzie, Lachunn Angus (UiT The Arctic University of Norway, 2021)
Broodstock nutrition has been shown to influence the performance of eggs and larvae in marine finfish. The present study aimed to test the hypothesis that a broodstock conditioning diet with increased astaxanthin, taurine and water would have an effect on the early life stages in Atlantic cod. Thus, cod broodstock were fed two diets, a standard broodstock conditioning diet, and an experimental diet containing an additional 30ppm astaxanthin, 1% taurine and 10% dietary water. During the experimental period, egg and larvae samples from three families for each diet were collected, and fertilization success, hatching success, larval length, weight and survival were recorded as well as biochemical analysis on fatty acid composition. Sperm samples were collected, and performance parameters were assessed using CASA. No differences were found in the performance of the two diets. This was in part due to large genetic differences within families of the same dietary group.